Technically sleeping? A clinical single-case study of a commercial sleep robot - Støre, Siri Jakobsson; Tillfors, Maria; Wästlund, Erik; Angelhoff, Charlotte; Clarke, Annika Norell (Frontiers in Psychology, 2022)
The Somnox sleep robot is promoted as sleep enhancing. The current study investigated individual effects, the acceptability and the safety of, and experiences with, a three-week intervention in adults with insomnia. A repeated ABA single-case design (n=4) was used to evaluate the effects of the sleep robot compared with baseline, as measured with a sleep diary and actigraphy. Pre-, post- and 1-month follow-up assessments were conducted, measuring symptoms of insomnia, level of somatic arousal, and symptoms of depression and anxiety. Questions about adherence were included in the sleep diary. Individual interviews were conducted post intervention to explore the participants’ experiences with the sleep robot. The sleep diary and actigraphy data showed marginal differences, and if something, often a slight deterioration in the intervention phase. Three participants reported improvements regarding their sleep in the interviews compared with baseline, which mirrored the results on the questionnaires (insomnia, arousal) for two of the participants. The same three participants adhered to the intervention. Stable or improved self-assessed symptoms of depression and anxiety, and information from the individual interviews, suggest that the intervention is safe for adults with insomnia. The results regarding the effects of the sleep robot were mixed, and ought to be scrutinized in larger studies before confident recommendations can be made. However, the study supports the acceptability and safety of the intervention in adults with insomnia.